FA’ALIYAH AL-TAQSHISH WA AL-TARFIH FI SARDI AL-HIKAYAH AL-KHURAFIYAH BATHAL ATENA: DIRASAH SARDIYAH GERARD GENETTE - Rif'ah, Mar’atun Nailur; Masadi, M. Anwar (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
A fairy tale is a type of folk literature with many elements, it comes from different district, region and tribe. Many people use it as a means of teaching children since it is entertaining and educational, so that children can understand it easily. The tale of the hero of Athena is one of the tales that we know today from the work of Kamel Kilani, the pioneer of children's literature. This tale has its own structure divided into several chapters and subsections, which contradicts to the common fairy tale which has no division. The analysis aims to identify the narrative structure, and the writer's way of conveying moral values and entertaining children. It is a qualitative research with the main data source is The Tale of the Hero of Atena by Kamel Kilani, published by the Hindawi Foundation for Education and Culture. The secondary source is books on the narrative structure of Gérard Genette. Data is collected using the technique of reading notes. The analysis begins by dividing the units of the story and ends with a description of the story line and point of view. The finding shows the effectiveness of the tale in conveying moral values and entertaining readers through a simple story line and a different point of view